Implementasi Suasana Surabaya Tempo Doeloe Pada Interior Pusat Kuliner Khas Jawa Timur - Giovani Tanza; Ronald Hasudungan Irianto Sitindjak; Hendy Mulyono (Intra, 2019)
The currently booming culinary business in Surabaya opens a very good opportunity to bring the East Javanese cuisine as a different variety. The purpose of this design is to provide a restaurant facility that can be used by the people to gather with their families, relatives, and colleagues and to create the interior of the culinary center that displays East Javanese ambiance which is represented by the city of Surabaya in this era of globalization. The method used in the design is Design Thinking Process. The concept of the design is “wani”, which is a word that represents the spirit and atmosphere of both the old and new City of Heroes, Surabaya. This interior design will bring a self-service system as the implementation of “wani” to plant a new habit and to grow self-awareness in the Surabaya society, both towards other people and their environment. In the end, the Interior Design of The East Javanese Culinary Center in Surabaya can be a facility to conserve the East Javanese culinary identity and also Surabaya as the city of heroes. Furthermore, the implemented self-service system is expected to bring back the behavior in the people of Surabaya, as well as a ‘tempo doeloe’ ambiance between the seller and the buyer.